Telaah Kelayakan Isi dan Bahasa Buku Tematik Terpadu Kelas 1 Kurikulum 2013 Terbitan Erlangga - Fika Salsabilla Madani; Dewi Utami; Iis Humaeroh (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This study examines the feasibility of content and language that pays attention to and evaluates based on the regulations of the National Education Standards Agency (BSNP) in Indonesia. The purpose of this study was to identify and describe the accuracy and appropriateness of the eligibility of the content and language in this thematic book published by Erlangga based on the eligibility criteria of the BSNP regulations. This research method uses a qualitative approach of literature study research. Data collection technique is done by documentation. The results showed that the eligibility of the content was feasible to use, the components of the suitability of the material with Core Competencies (KI) and Basic Competencies (KD) got a percentage of 71.87, the suitability of the material with the curriculum was 68.75%, the material accuracy component was 75%, and the learning support component of 75%. So the overall eligibility of the content in the Integrated Thematic Textbook for class 1 SD/MI curriculum 2013 published by Erlangga gets a percentage of 73.26%. The feasibility of the language is very feasible to use, the component of language use that is in accordance with the level of development of students gets a percentage of 100% with a very appropriate category, the use of communicative language is 91.67% with a very feasible category, the components of coherence and coherence are 100% with very decent category. So the overall language eligibility in the Integrated Thematic Textbook for class 1 SD/MI curriculum 2013 published by Erlangga gets a percentage of 96.42% in the very decent category.